STRATEGI INDONESIAN TRADE PROMOTION CENTER (ITPC) CHICAGO DALAM MENDORONG EKSPOR KOPI INDONESIA KE AMERIKA SERIKAT - Salu, Mentari Hanaya; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study focuses on the economic diplomacy strategy implemented by the Indonesian Trade Promotion Center (ITPC) Chicago as an extension of Indonesian state institutions in the United States, aimed at enhancing the export of Indonesian coffee to the United States. Indonesia is the world's fourth-largest coffee producer, and the United States is the largest destination for Indonesian coffee exports. Indonesian coffee exports to the United States have experienced a decline and various obstacles, necessitating the adoption of an effective strategy to address these challenges. The research employs a descriptive qualitative methodology, utilizing various data collection techniques, including literature review from books, journals, websites, and related documents. The study adopts the perspectives of liberalism, economic diplomacy theory, and the nation-state analysis level. The findings of this study indicate that the economic diplomacy strategy executed by ITPC Chicago is carried out through four stages of economic diplomacy: salesmanship economy, the formation of economic networks and advocacy, image building, and regulation management and resource mobilization. As a result, there has been an increase in Indonesian coffee exports to the United States, as ITPC Chicago has contributed to enhancing the coffee export chain to the U.S. through promotional strategies at coffee exhibitions, expanding business networks between exporters and importers in the United States, and providing market information services in the form of coffee market reports. Keywords: Economic Diplomacy, Exports, Coffee, ITPC, Indonesia, United States..